Endothelin-1 triggers oxidative stress and cytokine release in human microglia cells through ETRB-dependent mechanisms - Inostroza-Nieves, Yaritza; Bou, Shakira; Alvarado, José; Capo-Ruiz, Diego; Garcia, Jessica; Moliere, Jean P.; Arenas, Claudia P. (Frontiers in Cellular Neuroscience, 2025)
Microglial cells are highly specialized cells of the central nervous system (CNS) that play dual roles in neuroprotection, but can also promote inflammation and neurodegeneration. Endothelin-1 (ET-1) is a potent vasoconstrictor that induces severe and prolonged cerebral vasoconstriction and inflammation. However, the mechanism of how ET-1 activates a proinflammatory response in the CNS is unknown. In this study, we demonstrate that ET-1 activates proinflammatory and oxidative stress responses in human HMC3 microglial cells via endothelin receptor B (ETRB). ET-1 treatment significantly increased nitric oxide (NO) and reactive oxygen species (ROS) production, and upregulated inducible nitric oxide synthase (iNOS) mRNA. These effects were attenuated by the selective ETRB antagonist BQ788, but not by the ETRA antagonist BQ123, suggesting a receptor-specific mechanism. ET-1 increases TNFα levels by 56% (p = 0.0003) and IL-6 levels by 86% (p = 0.0111), and the effect was decreased to basal levels in the presence of BQ788. Moreover, ET-1 induced phosphorylation of STAT1 (3.5 folds, p < 0.0001), a transcription factor associated with microglial proinflammatory polarization. To validate the in vivo relevance of this pathway, we analyzed brain tissue from experimental autoimmune encephalomyelitis (EAE) mice. We found increased expression of Edn1 and Ednrb, as well as elevated ET-1 protein levels. These results identify ET-1/ETRB signaling as a key driver of microglial activation and oxidative stress, highlighting its potential as a therapeutic target in neuroinflammatory disorders.